Information technology investment and business performance: The role of management practices - PHAM, Chi Thi Bich; HOANG, Ha Thi Thu; DINH, Dung Thuy (International Journal of Innovative Research and Scientific Studies, 2025)
Vietnamese firms have invested heavily in information technology, which creates a rapid transformation in the digital world, aiming to enhance productivity and streamline operations. This investment could also allow businesses to improve their decision-making. However, the impact of information technology investment on firm performance remains inconclusive, particularly in emerging markets where institutional and managerial factors play a crucial role. This study investigates the impact of information technology investment on firm performance in the Vietnamese context. We also explore the moderating role of management practices in the above relationship. We collect data for 216 listed firms on the Ho Chi Minh City Stock Exchange in Vietnam over a period of five years from 2018 to 2022. Fixed-effects regression and 2SLS regression methods are employed to explore both the direct effect of information technology investment and the moderating impact of corporate management practices. Our results reveal that investment in information technology has a positive impact on firm performance, but its influence is significantly enhanced when supported by robust corporate management.